Influence of extreme concentrations of hydrophilic pore-former on reinforced polyethersulfone ultrafiltration membranes for reduction of humic acid fouling - Son, Moon; Kim, Hayoung; Jung, Junhyeok; Jo, Sungsoo; Choi, Heechul (Chemosphere (Oxford), 2017)
To address the issue of membrane fouling by ubiquitous humic substances, a hydrophilic pore-former–blended polyethersulfone UF membrane was successfully synthesized via the phase inversion method. For the first time, extremely high concentrations of polyvinylpyrrolidone (PVP), up to 20 wt%, were tested as the hydrophilic pore-former in order to determine the optimum concentration for humic acid fouling. Intrinsic membrane parameters such as permeability and selectivity were evaluated using a cross-flow UF filtration setup. Interestingly, as little as 1 wt% added PVP can significantly improve membrane permeability. That tiny amount of added PVP increased membrane flux to 1107 L/m2h·bar from zero flux, with over 90% rejection of humic acid. In addition, pure water permeation increased to over 2400 L/m2h·bar without sacrificing humic acid rejection (around 90%) when 10 wt% PVP was added; pure water permeation decreased to around 1000 L/m2h·bar as added PVP was increased to 20 wt%. The order of water flux increased with the amount of added PVP up to 20 wt% during humic acid fouling while maintaining membrane selectivity. However, the membrane with 10 wt% added PVP showed the best fouling resistance in terms of flux recovery ratio (98%), total flux loss, reversible fouling ratio, and irreversible fouling ratio. Therefore, the addition of 10 wt% PVP is recommended considering cleaning efficiency and the moderately high flux during humic acid fouling for field operation in wastewater reclamation and water treatment processes. [Display omitted] •A PVP blended PES UF membrane was successfully synthesized.•The performance of membranes with extremely high ratios of PVP was evaluated.•Detailed fouling mechanism and resistance toward humic acid were revealed.•Irreversible fouling caused by humic acid was reduced to 1/10.•Optimum PVP concentration for water treatment process was suggested.